(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This research paper examines the role of clusters in the German economy, their types, and the types of products they produce. It presents the views of leading researchers on clusters. The results of implementing a cluster system in several industrial sectors in the country are described in detail.